Student Stress Levels in Preparing Thesis - Livana PH; Dona Yanuar Agus Santoso; Sri Mulyani; Uswatun Hasanah (Indonesian Journal of Global Health Research, 2023)
Students in writing their theses face several obstacles that cause stress. The stressors faced by students vary so that students' stress responses can be categorized according to their levels. The research aims to determine the stress level of students in writing their theses at STIKES Kendal. This research is quantitative research with a descriptive analytical design. The sample for this research was 48 final year students who were writing their thesis. The sampling technique uses purposive sampling. The data collection tool used a questionnaire with 7 statements related to stress taken from the Depression Anxiety and Stress Scale 21 (DASS 21) questionnaire. The results showed that the majority of students in preparing their thesis were at a moderate level of stress with responses that were difficult to rest, easily agitated, and easily offended.